ESTIMATION OF HYDROCARBON DISTRIBUTION IN âBASKETâ FIELD USING ELASTIC IMPEDANCE INVERSION AND AVO ANALYSIS - Djabar Immanuel, David
“BASKET” Field is one of the oil and gas producing fields located in the Mahakam Block, Kutai Basin, East Kalimantan, offshore environment. The “BASKET” field has been producing oil and gas since 1974. This research is intended to identify a gas reservoir that was at the MF8.5-MF9 interval in the Kampungbaru Formation dominated by quartz sandstone intercalated shale. This research was conducted to determine the depositional environment, facies distribution, and to determine the distribution of hydrocarbon as a basis for recommendation of development well points around EB-1 wells, that have high DST. In this research, reservoir zones are distinguished from non reservoir based on elastic rock parameters, namely low elastic impedance. In turn, the seismic data consisting of near, mid, far had its bandwith been equated first, using the Spectral Balancing process to optimize the results of the inversion process. Furthermore, picking horizon is used to interpret the structure and stratigraphy in Post Stack data. Wells that were used are only those that have Vs data, so the wavelet making, and log transformation are performed only on EB-1 wells. AVO modeling was made at this well in the target area with two cases, namely gas saturated sandstone and water saturated sandstone, additionally, contained in this field, is AVO class 3 model at gas sand intervals. Seismic response of AVO class 3 models gives more detailed information on the fluid content at far offset. Therefore, the inversion process is only done on the far stack. Initial model development is done by interpolating the Elastic Impedance log and horizon that have been interpreted and transformed before. After the initial model and inversion wavelet are done, the Elastic Impedance inversion can be performed. The result of the inversion process is EI inverted cube. Using this classification, a slicing will be made to see gas sand distribution.